1985
DOI: 10.1007/bf00123541
|View full text |Cite
|
Sign up to set email alerts
|

Quinones as plant growth regulators

Abstract: The effects of benzoquinone, naphthaquinone and anthraquinone on the growth of tomato callus, whole plants of tomato and on rooting of mungbean cuttings were studied. Naphthaquinone effects on some oxidases and on the isozyme patterns of peroxidases in all the three systems were also observed. Quinones increased callus growth, the number of roots initiated in mungbean cuttings and the growth of tomato plants, significant increases being obtained with 10-s M naphthaquinone. Naththaquinone also decreased the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…There is an additional potential bene®t to gall-formers from high levels of phenolics in gall tissue. Phenolic compounds have been found to be manipulators of gene expression, plant hormone activity and hence plant growth (Ray and Laloraya 1984;Ranade and David 1985;Prinsen et al 1991), all processes gall-formers would seem likely to bene®t from manipulating. Furthermore, other tumour-forming processes, such as the nodulation of plant roots by Rhizobium, have been shown to involve phenolic compounds as``signals'' between the plant and the invading organism (Lynn and Chang 1990;Dakora et al 1993;Heidstra and Bisselling 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There is an additional potential bene®t to gall-formers from high levels of phenolics in gall tissue. Phenolic compounds have been found to be manipulators of gene expression, plant hormone activity and hence plant growth (Ray and Laloraya 1984;Ranade and David 1985;Prinsen et al 1991), all processes gall-formers would seem likely to bene®t from manipulating. Furthermore, other tumour-forming processes, such as the nodulation of plant roots by Rhizobium, have been shown to involve phenolic compounds as``signals'' between the plant and the invading organism (Lynn and Chang 1990;Dakora et al 1993;Heidstra and Bisselling 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The washing in acetone was part of the preparation of the enzyme extract [20] . This observation implies that 4-CR is bound tightly or maybe even irreversibly to the enzyme .…”
Section: Discussionmentioning
confidence: 99%
“…The soluble protein fraction was prepared from the hypocotyls [20] by a procedure involving washing of the extract in 50% (V/V) cold acetone, which removed the phenolics and precipitated the soluble protein . PPO was assayed using 4-methyl-catechol as a substrate and measuring the initial rates of the reaction at 410nm [15] .…”
Section: 3 Ppo Assaymentioning
confidence: 99%
“…In our studies, both the monophenols appear to be biologically active since they increased pod yields significantly over the control. In recent years, several studies have shown a general lack of correlation between the effects of phenolic compounds on growth and development and their structural configuration (12,13,21,22). In peanut if full pod load is established earlier and synchronous development ofpods with continuous supply of photosynthates maintained, pods formed are larger (16).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the last decade, their use has been expanded to several plant processes (2,6,7,12,13) with beneficial results (21,23). In earlier work we reported that some of the phenolic compounds (monophenols) were highly effective for yield improvement in some peanut cultivars, viz.…”
mentioning
confidence: 99%